MULTIVARIATE CALIBRATION METHOD FOR SIMULTANEOUS ESTIMATION OF FLUOCORTOLONE CAPROATE, FLUOCORTOLONE PIVALATE AND CINCHOCAINE HCL IN SUPPOSITORY - Donmez, Ozlem Aksu (UNIV BABES-BOLYAI, 2019)
In this paper, the simultaneous quantitative assay of Fluocortolone caproate (FCC), Fluocortolone pivalate (FCP) and Cinchocaine HCl (CIN) in suppository has been reported as a simple alternative analytical method. A partial least squares (PLS-2) regression was used for resolution of the overlapped spectrophotometric signals from mixtures of the three drugs. A calibration set containing FCC, FCP and CIN was constructed by using 3(3) full factorial design in the concentration range of 4.5-8.5, 5-7 and 8-12 mu g/mL, respectively. Absorption spectra were recorded in the range 240-350 nm. To check the quality of the proposed method, it was applied to the determination of these compounds in synthetic mixtures and pharmaceutical formulation, suppository. The PLS-2 method yielded recoveries ranging from 91 to 106%. The results compared well with those from the reported HPLC method.
Keywords: fluocortolone caproate; fluocortolone pivalate; cinchocaine HCl; PLS; PARTIAL LEAST-SQUARES; SPECTROPHOTOMETRIC DETERMINATION; VOLTAMMETRIC DETERMINATION; CHEMOMETRIC METHODS; LOCAL-ANESTHETICS; CHROMATOGRAPHY; DIBUCAINE; HYDROCHLORIDE; PARACETAMOL; HYDROCHLOROTHIAZIDE; Chemistry